2004
DOI: 10.1126/science.1101909
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of JNK2 for Scavenger Receptor A-Mediated Foam Cell Formation in Atherogenesis

Abstract: In vitro studies suggest a role for c-Jun N-terminal kinases (JNKs) in proatherogenic cellular processes. We show that atherosclerosis-prone ApoE-/- mice simultaneously lacking JNK2 (ApoE-/- JNK2-/- mice), but not ApoE-/- JNK1-/- mice, developed less atherosclerosis than do ApoE-/- mice. Pharmacological inhibition of JNK activity efficiently reduced plaque formation. Macrophages lacking JNK2 displayed suppressed foam cell formation caused by defective uptake and degradation of modified lipoproteins and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
238
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(254 citation statements)
references
References 27 publications
13
238
1
2
Order By: Relevance
“…Indeed, pharmacological inhibition of jnk or macrophage specific deletion of jnk reduced atherosclerosis in murine models, and atherosclerosis is also reduced in lyn KO mice. Activation of jnk also controls scavenger receptor A I/II (SRA) macrophage phagocytic activity (Ricci, et al, 2004). This report showed that inactivation of jnk trapped SRA on the cell surface and reduced binding and uptake of modified LDL.…”
Section: Cd36 Signalingmentioning
confidence: 97%
“…Indeed, pharmacological inhibition of jnk or macrophage specific deletion of jnk reduced atherosclerosis in murine models, and atherosclerosis is also reduced in lyn KO mice. Activation of jnk also controls scavenger receptor A I/II (SRA) macrophage phagocytic activity (Ricci, et al, 2004). This report showed that inactivation of jnk trapped SRA on the cell surface and reduced binding and uptake of modified LDL.…”
Section: Cd36 Signalingmentioning
confidence: 97%
“…There is a striking increase in JNK activity at crucial metabolic sites such as adipose and liver tissue in mouse models of obesity 86 . Most importantly, JNK deficiency protects mice from insulin resistance, fatty liver and diabetes 86 , which implies that JNK inhibition might be a promising therapeutic avenue for diabetes [87][88][89] .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…JNK deficiency has been reported to protect mice from insulin resistance, fatty liver and diabetes 86 , and inhibition of JNK is considered to be a promising therapeutic avenue [87][88][89] . Similarly, mouse models harbouring null mutations in IKK have validated that this kinase impacts insulin signalling, and inhibition of IKK by high-dose salicylates improves insulin action in experimental models and humans 90 .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…DiI-labeled LDL particles were ultracentrifuged, collected, dialyzed, and sterilized to remove the DiI particulate [33]. BAEC were treated with 10 µg/ml DiI-labeled LDL at 0°C for 90 min or at 37°C for 4 h for LDL binding or uptake experiments, respectively [33].…”
Section: Binding and Uptake Of Ldl Particlesmentioning
confidence: 99%
“…DiI-labeled LDL particles were ultracentrifuged, collected, dialyzed, and sterilized to remove the DiI particulate [33]. BAEC were treated with 10 µg/ml DiI-labeled LDL at 0°C for 90 min or at 37°C for 4 h for LDL binding or uptake experiments, respectively [33]. Cells were also treated with10 µg/ml DiI-labeled LDL with 200 µg/ml of excess unlabeled LDL as a control to exclude DiI labeling of cell membranes and for LDL binding and uptake specificity [33].…”
Section: Binding and Uptake Of Ldl Particlesmentioning
confidence: 99%